Optimal decisions in reducing loss rate of returnable transport items. (20th March 2019) - Fan, Xiangxiang; Gong, Yeming; Xu, Xianhao; Zou, Bipan
Abstract: Returnable transport items (RTI) have been commonly used due to their advantages in reducing packaging waste and improving supply chain sustainability. However, RTI loss will result in a mismatch between the products flow and the RTI supply, which will affect operational continuity. This paper studies a RTI supply chain consisting of a single manufacturer and a single retailer, assuming that the retailer can reduce RTI loss by investing in staff training. We first develop an inventory model to minimize the total cost of the system. Then we analyze the optimal decision of the closed-loop supply chain of RTI. We compare the case where the retailer invests in reducing RTI loss and the case where the retailer does not. The results show that the supply chain will be more efficient if the retailer invests in reducing RTI loss, and the total cost of the system will be reduced. However, the retailer will invest only when its cost decreases. Thereby, we consider side payments as an available incentive to stimulate the retailer to invest. Moreover, we build an asymmetric Nash bargaining model considering investment cost sharing to coordinate the RTI supply chain. We compare the total optimal cost of the manufacturer and the retailer. The results show that the system can be coordinated, and the optimal total costs of both the manufacturer and the retailer are reduced. Highlights: We consider the retailer's investment in reducing the loss rate of returnable transport items. An inventory model is formulated to optimize the system performance. The supply chain will be more efficient if the retailer invests. We use side payments to stimulate the retailer to invest. An asymmetric Nash bargaining model is developed to coordinate the supply chain.